Pull-Push: Market and consumer interventions to improve food safety in Ethiopia and Burkina Faso - Knight-Jones, Theodore J.D.; Amenu, Kebede; Tacken, G.; Ilboudo, Guy S.; Madjdian, D.; Girma, S.; Ibrahim, A.M.; Grace, Delia; Vet, E. de; Dione, Michel M. (International Livestock Research Institute, 2022)
Objective: Working in informal food markets in Africa we test if consumer demand for safe food can be generated and utilised to drive improved standards of hygiene and safety up the value chain. Materials and methods: Following food safety value chain assessments and KAP surveys, large consumer awareness campaigns were launched in Ouagadougou, Burkina Faso (chicken) and Harar, and Dire Dawa, Ethiopia (tomato). These multimedia campaigns are implemented by commercial advertising/communication agencies, and comprise TV and radio adverts, door-to-door household visits and social media, including using social influencers to promote food safety messages. The messages focus on purchasing quality, hygienic foods and following basic food safety rules. Baseline consumer surveys were conducted to assess consumer consideration of food safety when making food purchases. This will be compared to endline surveys to be conducted in 2023. This work is performed within the Pull-Push project. Results: Hygiene standards in the target food value chains have major weaknesses. Before the campaign consumer consideration of food safety was variable in Ethiopia and Burkina Faso, with greater concern in high income groups. There was a disproportionate concern about chemical hazards in vegetables and to a lesser extent chicken. Results of the communications campaign’s impact on food choice will be available in 2023. Conclusion: Although foodborne disease exerts a massive health and economic burden on developing countries, there is a lack of application of food safety standards. Furthermore, consumers continue to source food from outlets with poor hygiene. If a communications campaign can influence consumers so they purchase safer foods, forcing suppliers to improve standards, this will provide a way of improving food safety in the informal sector where most people in Sub-Saharan Africa source their food, and where efforts to improve food safety have so far had limited impact.